Isolation and Characterization of the Roots of Rumex nervosus - Gashaw Nigussie (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
Rumex nervosus belongs to the family of Polygonaceae,which is traditionally used in Ethiopia to treat various diseases. This prompted us to isolate bioactive compounds from the root of this plant. Ground root parts of Rumex nervosus were subjected to exhaustive extraction successively with petroleum ether and methanol.The solvent from each extract was evaporated under reduced pressure using rotavapour to obtain petroleum ether and methanol extract. Chromatographic purification of the methanol extracts by Column chromatography followed by Preparative Thin layer Chromatography using Chloroform: methanol (9.5:0.5) ratio gave a compound coded as RN-6. The structure of this compound 4-ethylheptyl benzoate was characterized as by means of 1H NMR, 13C NMR, UV and IR spectral data.